2005
DOI: 10.1007/s10541-005-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase Pathway of Arachidonic Acid Metabolism in Growth Control of Tumor Cells of Different Type

Abstract: The influence of inhibitors of different lipoxygenases (LOX) on the growth of human tumor cells with different profiles of synthesized eicosanoids was studied. The studied LOX inhibitors had virtually no influence on the growth of A549 cells actively synthesizing cyclooxygenase and lipoxygenase metabolites of arachidonic acid (AA). The inhibitor of 12-LOX, baicalein, significantly inhibited proliferation in cultures of A431 epidermoid carcinoma cells with a characteristic domination of the major lipoxygenase m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Further, specific 12‐LOX inhibitor, baicalein, and COX‐2 inhibitor, celecoxib, alone or in combination, effectively suppressed the growth of A431 cells and significantly lowered the incorporation of thymidine into DNA. The addition of exogenous 12‐(S)‐HETE, on the other hand, increased the incorporation of thymidine into DNA in a dose‐dependent manner which was in accordance with the earlier report (19). A similar increase in the proliferation of prostate (20) and gastric cancer cells (21) was reported in response to 12‐(S)‐HETE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, specific 12‐LOX inhibitor, baicalein, and COX‐2 inhibitor, celecoxib, alone or in combination, effectively suppressed the growth of A431 cells and significantly lowered the incorporation of thymidine into DNA. The addition of exogenous 12‐(S)‐HETE, on the other hand, increased the incorporation of thymidine into DNA in a dose‐dependent manner which was in accordance with the earlier report (19). A similar increase in the proliferation of prostate (20) and gastric cancer cells (21) was reported in response to 12‐(S)‐HETE.…”
Section: Discussionsupporting
confidence: 92%
“…Most tumor cells produce AA metabolites and these compounds have been found to modulate a wide range of biological factors that induce growth and invasiveness of tumors (7). Recent investigations have shown that tumors of different histogenesis differ considerably in the metabolism of AA (19). Consequently, the expression and role of the AA metabolizing enzymes would be different in different cancers, thus necessitating an understanding of the expression profile of AA metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Resting A549 lung [30] and Caco-2 colon [31] cancer cells likewise localize cPLA 2 α to internal membranes. Since PC3, MDA-MB-231, A549, and Caco-2 cells overproduce eicosanoids or platelet-activating factor and use these products to promote their own growth [27,[32][33][34][35], constitutive localization of cPLA 2α to membranes may underlie the over-production of PL-derived mediators and thereby certain aspects of the malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, baicalein induced apoptosis in renal cell carcinomas in time‐ and concentration‐dependent manner (33). For these reasons, we assume that 12‐LOX pathways play an important role in cancer cell survival (34), and its inhibition might be an effective co‐therapy to hypericin‐mediated PDT.…”
Section: Discussionmentioning
confidence: 99%